Motivating Learners through Project-Based Learning - Faizah, Mohamad Nor (INTI International University, 2007)
Project-based learning (PBL) is a learning approach that moves away from classroom, teacher-centered activities and instead focuses on learner-centered tasks which are integrated with real world issues and practices. This learning approach, which has been around for some time, is introduced into an English course offered to leaners following the third-stage English Language programme at a higher learning institution. This paper describes the PBL task which these language learners carried out in groups. The task is conducted outside the classroom whereby learners are required to meet real-world professionals to gain information pertaining to their future careers. A study was conducted to investigate what the learners felt about this component embedded in the course, and to what extent PBL has motivated them in their learning. This paper also discusses the short and long-term gains learners reap from the learning approach.